The taxonomic status of badgers (Mammalia, Mustelidae) from Southwest Asia based on cranial morphometrics, with the redescription of Meles canescens - Abramov, Alexei V.; Puzachenko, Andrey Yu. (Zootaxa, 2013)
The Eurasian badgers (Meles spp.) are widespread in the Palaearctic Region, occurring from the British Islands in the west to the Japanese Islands in the east, including the Scandinavia, Southwest Asia and southern China. The morphometric vari-ation in 30 cranial characters of 692 skulls of Meles from across the Palaearctic was here analyzed. This craniometric anal-ysis revealed a significant difference between the European and Asian badger phylogenetic lineages, which can be further split in two pairs of taxa: meles – canescens and leucurus – anakuma. Overall, European badger populations are very sim-ilar morphologically, particularly with regards to the skull shape, but differ notably from those from Asia Minor, the Mid-dle East and Transcaucasia. Based on the current survey of badger specimens available in main world museums, we have recognized four distinctive, parapatric species: Meles meles, found in most of Europe; Meles leucurus from continental Asia; M. anakuma from Japan; and M. canescens from Southwest Asia and the mountains of Middle Asia. These results are in agreement with those based on recent molecular data analyses. The morphological peculiarities and distribution range of M. canescens are discussed. The origin and evolution of Meles species, which is yet poorly understood, is also briefly discussed.